Clinical study of thyroid swellings - Rathod, Ashwini S.; Ghate, Girija A.; Korah, Ammu; Krishnan, Lakshmi; Dashora, Ruchir R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Thyroid swellings are very frequently encountered in ENT practice, ranging from a simple cyst to a malignant tumour. Disorder of structure of thyroid gland, due to various etiological factors, will give rise to swelling in the neck region. Clinical signs and symptoms are inadequate to diagnose thyroid disorders as similar presentations are seen in various thyroid disorders. So, this study of thyroid swellings was done to know different clinical presentations, age and sex distribution, correlation between thyroid swellings and thyroid function tests, analyse various thyroid swellings and etiological factors based on pathological reports. Methods: A prospective study with 50 patients of thyroid swellings was conducted over 2 years, after taking consent from each patient. Patients were clinically examined by inspection, palpation, percussion, auscultation and underwent thyroid function tests. Ultrasonography (USG) and fine needle aspiration cytology (FNAC) was done in all patients. Results: Total 50 patients of thyroid swellings were studied. Mean age of the patients was 38.92 years with female preponderance (74%). Thyroid swellings were commonly present bilaterally (54%). 82% cases showed euthyroid state. USG revealed that most of the patients had colloid nodule (46%), followed by MNG (26%). Majority of lesions were benign on both USG and FNAC reports. MNG (44%) was reported frequently in the provisional diagnosis, followed by colloid nodule (24%). Conclusions: In all cases of thyroid swellings, detailed clinical history, thorough clinical examination is required. Thyroid function test, USG and FNAC reports help to reach the definitive diagnosis. Histopathological report confirms and gives final diagnosis.